2013
DOI: 10.1016/j.clnu.2012.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and poor food intake are associated with prolonged hospital stay, frequent readmissions, and greater in-hospital mortality: Results from the Nutrition Care Day Survey 2010

Abstract: Malnutrition and poor food intake are associated with prolonged hospital stay, frequent readmissions, and greater in-hospital mortality: Results from the nutrition care day survey 2010 Ekta AgarwalThe University of Queensland Maree Ferguson Princess Alexandra Hospital Merrilyn Banks Royal Brisbane & Womens Hospital Marijka Batterham University of Wollongong Judith BauerThe University of Queensland Recommended Citation Agarwal, E., Ferguson, M., Banks, M., Batterham, M., Bauer, J., Capra, S., & Isenring, E. (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
366
4
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 399 publications
(417 citation statements)
references
References 26 publications
17
366
4
18
Order By: Relevance
“…In terms of screening (usually completed by nursing staff or diet clerks), less than half of patients were screened for malnutrition risk at admission. This is consistent with other research indicating that nutrition screening rates are generally poor, ranging from 42% of patients [36] to 64% [10]. Three of the five hospital sites were routinely screening, with only two having relatively good completion rates (76 and 66% of patients) and using validated tools.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In terms of screening (usually completed by nursing staff or diet clerks), less than half of patients were screened for malnutrition risk at admission. This is consistent with other research indicating that nutrition screening rates are generally poor, ranging from 42% of patients [36] to 64% [10]. Three of the five hospital sites were routinely screening, with only two having relatively good completion rates (76 and 66% of patients) and using validated tools.…”
Section: Discussionsupporting
confidence: 78%
“…A study conducted by the Canadian Malnutrition Task Force found that 45% of patients on medical or surgical wards who stayed more than 2 days were malnourished on admission [3]. Malnutrition often goes undetected [9], which is concerning as it increases mortality, length of stay, and risk of re-admission, even when considering other important covariates such as age, sex, socioeconomic and diseaserelated characteristics [3,[10][11][12][13][14][15]. Malnutrition also increases hospital costs [5,16,17] and in Canada, this is by approximately $2000CDN per malnourished patient when compared to a well nourished patient [18].…”
Section: Introductionmentioning
confidence: 99%
“…26,[35][36][37] Survival (or mortality) is the one of the most frequently measured variables related to nutrition. 10,28,29 One large new study showed that, to save a life, the numberneeded-to-treat (the average number of patients who need to be treated to prevent one additional bad outcome) with ONS was just 20.3. 30 In terms of cost-related outcomes, many studies examined the relationship between malnutrition and increased length of hospital stay and frequency, hospital readmission, and hospital episode costs.…”
Section: Resultsmentioning
confidence: 99%
“…9 Once admitted to the hospital, the malnourished individuals are more likely to experience complications (delayed wound healing, pressure ulcers, and infections), have longer hospital stays, and are at a greater risk of dying. 10,11 Medical nutrition, the clinical application of knowledge about the role played by nutrients in health and disease, is increasingly being used in interventions that have been shown to improve patients' quality of life and other health outcomes while also reducing overall health care costs. 4,7,12 Such cost reductions result from lowering the readmission rates, 13,14 decreasing the length of hospital stay, 15 reducing the frequency of complications (postsurgical infections and pressure ulcers), 12,16,17 and ultimately reducing the overall episode cost.…”
mentioning
confidence: 99%
“…Poor food intake is also common and results from multiple factors including poor food quality, food/eating preferences, feeling unwell and other disease side effects, as well as barriers to food intake, such as not being able to access the tray or requiring eating assistance [8,9]. Both poor hospital food intake and malnutrition lead to negative health outcomes including a longer length of stay, readmission, and comorbidities and mortality [3,7,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%